Analysis of the Influence of 4 A Components (Attraction, Accessibility, Amenity, Ancillary) and Social Media Marketing on Repeat Visit Interest and Visitor Satisfaction as an Intervening Variable (Case Study of Lawang Sewu Visitors ) - A’ardila Putri, Ari; Bayu Kurniawan,; Rita Meiriyanti, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research examines the influence of attraction, accessibility, amenities, ancillary and social media marketing on repeat visit interest on visitor satisfaction in Lawang Sewu. This research was conducted using quantitative research methods, the research population was visitors who had made tourist visits to Lawang Sewu Semarang. This research used a purposive sampling technique, and collected data from 110 respondents. The data collection method in this research uses a questionnaire with SEM (Structural Equation Modeling) analysis techniques on SmartPLS 3.29 software as a tool in research analysis. The research results show that Attraction, Accessibility, Amenity, Ancillary and Social Media Marketing have no effect on Repeat Visit Interest, then Attraction, Accessibility, Amenity, Ancillary and Social Media Marketing have an effect on Visitor Satisfaction and Attraction, Accessibility, Amenity, Ancillary and Social Media Marketing have an effect on Return Visit Interest which is mediated by Visitor Satisfaction